Antimony(V) Chloride as an Efficient Reagent for Deprotection of Methyl Ethers - Saadati, Fariba; Meftah-Booshehri, Hamid (Synlett, 2013)
This paper proposes a new and efficient method for the deprotection of methyl ethers using antimony pentachloride at ambient temperature. The procedure described here is a facile and practical method for the removal of the methyl group from aryl and benzyl methyl ethers. High selectivity was observed for the removal of the methyl group from dimethoxyarenes. The notable advantages of this protocol are mild reaction conditions, high yields, and the facility of workup procedure. The mechanism of the ether cleavage is proposed to explain this new reaction.
Keywords: demethylation; methyl ether; antimony pentachloride; selectivity; dimethoxyarenes